Wealth(s) and Subjective Well-Being - Brulé, Gaël; Suter, Christian (Social Indicators Research Series, 2019)
This volume examines the impact of wealth on quality of life and subjective well-being (SWB). As wealth is related to economic, environmental and social features of societies, this volume serves as an important resource in understanding economic and SWB. It further discusses a variety of experiences and consequences of inequalities of wealth. Through the availability of wealth data in recent international surveys, this volume explores the multiple relations between wealth and SWB. Structured around four main pillars the book presents analysis of the topic at various levels such as theoretical and conceptual, methodological and empirically, ending with a section on distribution and policies. .